Abbeyknockmoy Cistercian Monastery, loose stone fragments, jamb - O'Donovan, Danielle (My University, 2008)
Jamb fragment, possibly door. Moulding comprises: hollow chamfer, quadrant, right-angled rebate, hollow chamfer, quadrant.
Keywords: quadrant; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Cistercian; Late Medieval; moldings, hollow; roll mouldings